Knowledge, Attitude and Practice towards COVID-19 among Private School Teachers of Chitwan, Nepal - Dhakal, R. D.; Paudel, D.; Shrestha, P.; Adhikari, P. (Kathmandu University Medical Journal, 2021)
Background The coronavirus disease (COVID-19) pandemic has brought life to a standstill across the world, with nearly 178 countries reporting school closures. As the schools have started reopening slowly, precautions are utmost necessary to prevent the potential spread of COVID-19 in school and community settings. Objective To assess knowledge, attitude and practice towards COVID-19 among private school teachers. Method A web based cross-sectional analytical study design was undertaken. Currently working private school teachers of Chitwan District were included as a unit of analysis. The snowball sampling technique was employed to identify the eligible participant. Collected data was entered in SPSS version 20 and analyzed using the Chi-square test, Pearson correlation, and binary logistic regression. Result Of 344 participants, the majority were male (52.9%), most of the participants were from age group 26-30 years (38.4%). Regarding knowledge, attitude and practice, 57% had good knowledge, 53.2% had favorable attitude and 51.7% had good practice towards COVID-19. Logistic regression analysis demonstrated gender (OR 0.475, 95% CI: 0.256-0.818) and COVID-19 training (OR 25.687, 95% CI 5.354-123.226) were significant with good knowledge. Conclusion Knowledge about COVID-19 among private schools teacher was good, attitudes have been mostly favorable, and the practices were mostly adequate. However, good knowledge is not the only factor for better attitude and good practices. It is necessary to implement massive education campaigns, trainings and information via school authorities and health authorities by developing and adopting appropriate guidelines on COVID-19.